Regression Testingin Software Development (International Journal of Engineering and Computer Science, 2014)
Researchers have tried to make regression testing more effective and efficient by developing regression test selectiontechniques, but many problem remain, such as: Unpredictable performance, Incompatible process assumptions and inappropriate evaluation models. RTS techniques try to maximize average regression testing performance rather than optimize aggregate performance over many testing sessions. Regression testing is a crucial problem in software development as regression testing can be used not only for testing the correctness of a program, but often also for tracking the quality of its output. Both the research community and the industryhave paid much attention to this crucial problem. The paper try to do the surveyof current research on regression testing and current practice in industry and also try to find out whether there are gaps betweenthem. The observations show that although some issues are concerned both by the research community and the industrygay, there do exist gaps.